Generating high-resolution global unstructured meshes - Liu Zhuang; Huang Xiaomeng (Dianzi Jishu Yingyong)
The Spherical Centroid Voronoi tessellations(SCVT) are a kind of high-quality unstructured meshes, which are adopted by well-known earth system models at home and abroad. Internationally, the open source project Message Passing Interface SCVT(MPI-SCVT) has realized the parallel SCVT generation. However, although MPI-SCVT works well for the generation of general-resolution meshes, the use of MPI-SCVT presents several problems when the required mesh is of very high resolution, including the poor quality of initial mesh points, large data MPI communication problems, external library calling problems and I/O problems. For these problems, a set of solutions are proposed. Practice shows that the application of these solutions can successfully complete the generation of the global 1.9 km resolution grid, and the number of iterations is significantly reduced when reaching the same accuracy, which saves the calculation time.